Распределение температуры в трубном пучке при поперечном обтекании - Капинос, Василий Максимович; Пустовалов, Владимир Николаевич; Смородская, Инна Васильевна (ru, 2004)
At the cross-flow in a tube bundle in consequence of the gas temperature drop there is the different temperature of the tube walls. Because of that different heat deformations and stresses of the tubes arises, which can result in the failure of the tubes-plate juncture. The approximate method of the temperature distribution in a tube bundle is proposed.
Keywords: вальцовочные соединения; перекрестный ток; температурные удлинения; температурные напряжения; уравнение теплопроводности